Pedagogical Competence of PPG Graduate Teachers in Phase A Science Learning: A Phenomenological Study on the PAUD–Primary School Transition - Novia Wiranti; Edi Waluyo; Ali Formen (ISEJ : Indonesian Science Education Journal, 2026)
The transition from early childhood education (PAUD) to the first years of primary school is a decisive period for developing children's early scientific literacy. In Indonesia, graduates of the Teacher Professional Education Program (Pendidikan Profesi Guru/PPG) with a PAUD background are increasingly required to teach Phase A students in Grades 1 and 2, where play-based pedagogy must be reconciled with more structured science learning under the Kurikulum Merdeka. This phenomenological study explored the lived experiences of six PPG graduate teachers with PAUD academic backgrounds who taught Phase A classes in rural mountainous public primary schools in Magetan, East Java. Data were collected through semi-structured in-depth interviews, non-participant classroom observations, and document analysis. The data were analyzed using the Stevick-Colaizzi-Keen procedure as modified by Moustakas, involving bracketing, horizontalization, meaning-unit construction, thematic clustering, textural-structural description, and synthesis of the essence of experience. Four themes emerged: theoretical pedagogical awareness that was not fully translated into practice, monotonous learning with limited exploratory science activities, structural constraints in facilities and school support, and weak post-PPG mentoring. The findings show that PPG enhanced teachers' conceptual awareness of child development, lesson planning, and active learning; however, the enactment of these competencies remained constrained by limited science resources, administrative teaching routines, conventional school culture, and the absence of sustained professional assistance. The study contributes to early science education by showing that pedagogical competence is not an individual attribute alone, but a situated professional practice shaped by institutional, geographical, and cultural conditions. Strengthening post-PPG mentoring, inquiry-based science resources, and contextual transition curricula is therefore essential for improving Phase A science learning in rural mountainous schools.